Improving Creativity in College Students Through Physical Activities - Muhammad Kharis Fajar; Imam Marsudi; Ika Jayadi; Muhammad Labib Siena Ar Rasyid; Afif Rusdiawan (Universitas PGRI Palembang, 2022)
Physical activity not only improves health status and reduces disease, but also has benefits on individual cognitive function. Several studies state that regular physical activity can improve creative thinking, and cognitive factors are needed for invention and innovation. The purpose of this study was to determine the increase in creativity in college students through physical activity. This study uses an experimental approach in the field with an observational action pattern, the research design is two group pretest-posttest design. The population in this study were college students of class 2018, 2019, and 2020 at the department of Sport Coaching Education, State University of Surabaya. In this study using a purposive sampling technique which was divided into two groups, namely AB and AJ, and each group consisted of 30 college students, so that the total sample in this study as many as 60 college students. Pre-test and post-test using the E-Char application to determine the level of creativity. The results showed that post-test results in both groups increased creativity, but the highest increase occurred in the AJ group who had been given physical activity treatment for 14 meetings. The results of the Mann-Whitney difference test showed a value of p = 0.000 (<0.05) which concluded that there was a significant difference in groups AB and AJ. In conclusion, groups that do physical activity for 7 weeks with a frequency of 2 times per week (14 meetings) can increase college students creativity.